Gendered voices for climate action - Fisher, Susannah; Shakya, Clare (iied Working Paper, 2018)
Including local women and men who have experienced the impacts of clim ate change in decision-making forums is key to developing a just proce ss hearing local voices and experiences. The Paris Agreement signs up the international community to delivering countrydriven, gender-respon sive climate action. Including local women and men will be critical to this transition and to achieving the scale and pace of change needed through both procedural and distributional justice. However, there is scarce evidence on how these voices and experiences can impact on and strengthen climate responses, or how best to enable and facilitate thi s participation.